1968
DOI: 10.1111/j.1532-5415.1968.tb01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid‐femoral Pulse Wave Velocity*

Abstract: Simultaneous records of the pulse waves were obtained from the right common carotid artery and the right femoral artery by means of piezo-electric microphones in 26 per= sons whore ages ranged from 15 to 92 years. The time difference between the foot points of the waves from them two sites was termed Tar.A significant correlation was found between ToS and age, be= tween TOP and the systolic blood pressure and between Top and As described by Miller and White (1) and Geddes and Hoff (2), the pulse wave can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
3
4
0
1
Order By: Relevance
“…All that is required is the simultaneous recording of carotid and femoral pulse waves. Nielsen et al [19] have shown that the results from this method are comparable with those obtained by intra arterial measurement of PWV.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…All that is required is the simultaneous recording of carotid and femoral pulse waves. Nielsen et al [19] have shown that the results from this method are comparable with those obtained by intra arterial measurement of PWV.…”
Section: Discussionsupporting
confidence: 68%
“…At Nielsen et al [ 19] have shown that PWV calculated from these measurements agrees well with direct mea surement of PWV by aortic catheterisation. Table I shows the means and standard er rors of the results obtained in the different tests.…”
Section: Calculation O F Arterial Compliancesupporting
confidence: 57%
See 1 more Smart Citation
“…Elevated systolic blood pressure and pulse pressure play integral roles in cardiovascular outcomes such as left ventricular hypertrophy, ventricular failure, and the atherosclerotic process. Furthermore, systolic hypertension is a major risk factor for coronary heart disease, 143,144 stroke, 145 and cardiovascular 146 and total 147 mortality. Therefore, it is not surprising that measures of arterial stiffness also predict future cardiovascular risk in adults.…”
Section: Relationship To Cardiovascular Risk In Adultsmentioning
confidence: 99%
“…Dans quelle mesure cette altération est-elle compensée par la régulation de la fonction pompe apportée par le système nerveux autonome ? L'accroissement des pressions systoliques (PS) observé avec l'âge chez l'homme et l'animal [12,14] est-il la conséquence des modifications du myocarde, du circuit ou de la régulation nerveuse autonome?…”
unclassified